The Relationship between the Reorganization of Higher Education Institutions' Operations in Poland During the COVID-19 Pandemic and Student Loyalty - Sojkin Bogdan; Bartkowiak Paweł; Michalak Szymon (Marketing of Scientific and Research Organizations)
The aim of the study was to determine the nature of the relationship between the reorganization of higher education institutions in Poland, including the quality of online class delivery during the COVID-19 pandemic, and student loyalty - using the Net Promoter Score (NPS). Given the sudden transition to online learning, HEIs faced challenges in delivering educational continuity, with varying degrees of success across institutions. The study was conducted on a sample of 2,832 Polish students. Using exploratory factor analysis (EFA), the main components were identified for various variables pertaining to the functioning, organization, and delivery of online classes, as well as for aspects associated with university operations during the COVID-19 pandemic. In terms of administrative and organizational support, as well as technical and didactic assistance during the pandemic, universities were rated relatively highly. However, respondents held a slightly less favorable view of the atmosphere and practical value of online classes. The lowest ratings were given to the offerings for professional and academic development. Our findings also indicate a higher satisfaction among female and part-time students, and a positive correlation between administrative efficiency and student loyalty. The analysis also reveals that first-year students and graduate-level participants displayed higher loyalty, while loyalty tended to decrease with the length of study. In the area of student loyalty, the analysis of NPS indicates that first-year undergraduate students and graduate students exhibit a higher level of loyalty – the NPS values were positive, although overall relatively low. Regarding the factors influencing loyalty, the strongest correlations with student loyalty were observed in the case of the administrative and organizational efficiency of the university and the technical and didactic support in remote education – higher correlation values were recorded for female students and part-time students. These findings highlight critical areas for HEIs to address in enhancing stu-dent satisfaction and loyalty in a rapidly changing educational environment.